Relating to life and death a qualitative study of individuals with a long-lasting death wish related to unbearable psychiatric suffering - Sofie Verdegem; Anke Rens; Joris Vandenberghe; Jessie Dezutter; Thijs Vanhie; Luc Bemelmans; Siebrecht Vanhooren (International Journal of Qualitative Studies on Health & Well-Being)
Objective This study describes the lived experiences of persons with a long-lasting death wish related to unbearable psychiatric suffering (DWUPS) regarding their relationship to life and death. The findings are evaluated considering existing literature on suicidality and euthanasia, with a particular focus on the humanistic-existential perspective. Method An open-ended data-gathering strategy was employed to elicit comprehensive descriptive information about the phenomenon from ten in-depth interviews, applying the method of generic descriptive-interpretative qualitative research. Results Persons with DWUPS experience difficulties in connection with others, with themselves, with the world and with life itself. Concurrently, they indicate new possibilities for nascent connection in relation to others by receiving support and being able to share their death wish. This can result in growth in relation to themselves, in allowing hope, meaning and new engagement in life. The desire to die manifests itself in a variety of ways, including a strong and persistent death wish, an ambivalent attitude, or a temporary suspension of their death wish. Conclusion The process of exploring the death wish can assist persons with DWUPS in accessing potential ambivalence between life and death, in regulating emotional distress and in bearing existential concerns related to the life-and-death-questions.